2018
DOI: 10.1016/j.bbmt.2017.12.690
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Address Moral Distress Experienced by Stem Cell Transplantation Nurses and Build Resiliency

Abstract: level (<30 ng/ml). This demonstrates continued improvement in monitoring and supplementation as well as a sustained workflow (Figure 1). Cohort 2 included 162 patients: 85 autologous and 77 allogeneic. A vitamin D level was performed within 100 days of HSCT in 46% of patients and 19% were VDD. At 6 months post HSCT, 41% had a vitamin D level checked and 30% were VDD. Comparison with pretransplant levels showed that 87% of patients within 100 days and 82% of patients within 6 months had an increase in vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…First, we hypothesized that nurses would have higher MD than physicians. This scenario has been described as a stable trait of the MD scales and is likely related to the less powerful position nurses have in the units [ 8 , 14 , 25 , 29 , 30 , 31 ]. Second, we would expect healthcare providers considering leaving their position to have higher MD levels than the others, as already demonstrated in many previous studies [ 8 , 25 , 29 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, we hypothesized that nurses would have higher MD than physicians. This scenario has been described as a stable trait of the MD scales and is likely related to the less powerful position nurses have in the units [ 8 , 14 , 25 , 29 , 30 , 31 ]. Second, we would expect healthcare providers considering leaving their position to have higher MD levels than the others, as already demonstrated in many previous studies [ 8 , 25 , 29 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A review by Lamiani et al [41] has found that numerous studies, both quantitative and qualitative, have been published, and these publications mainly focused on nurses working in ICUs. It may be due to the deep-rooted proximity of the nurse-patient relationship and the relevant ethical aspects embedded in their involvement in endof-life care, which made moral distress a relevant experience for healthcare professionals [34,[41][42][43][44][45]. Another study by Nuttgens and Chang showed that moral distress may result from substandard supervision, supervisee vulnerability, supervisee non-disclosure, and organizational pressures [46].…”
Section: Discussionmentioning
confidence: 99%
“…3 Feelings of powerlessness, guilt, self-criticism, and low self-esteem from moral distress are reported. 1,[4][5][6][7][8][9][10][11] Negative effects associated with moral distress include avoiding patient interaction, placing blame on administration and coworkers, and experiencing long-term effects on their sense of moral conscience. 3 To address moral distress, Schwartz Center Rounds (SCRs) were implemented at a southeastern US level 1 trauma center and children's hospital.…”
mentioning
confidence: 99%
“…1,14 Although most ICU-based research has focused on nurses, moral distress in physicians, respiratory therapists, and pharmacists has also been examined, reflecting the breadth of moral distress in healthcare. 11,[15][16][17]…”
mentioning
confidence: 99%
See 1 more Smart Citation